DEEM, a versatile platform of FRD measurement for highly multiplexed fibre systems in astronomy. Issue 4 (24th February 2018) - Yan, Yunxiang; Yan, Qi; Wang, Gang; Sun, Weimin; Luo, A-Li; Ma, Zhenyu; Zhang, Qiong; Li, Jian; Wang, Shuqing
Abstract: We present a new method of DEEM, the direct energy encircling method, for characterizing the performance of fibres in most astronomical spectroscopic applications. It is a versatile platform to measure focal ratio degradation (FRD), throughput, and point spread function. The principle of DEEM and the relation between the encircled energy and the spot size were derived and simulated based on the power distribution model (PDM). We analysed the errors of DEEM and pointed out the major error source for better understanding and optimization. The validation of DEEM has been confirmed by comparing the results with conventional method which shows that DEEM has good robustness with high accuracy in both stable and complex experiment environments. Applications on the integral field unit (IFU) show that the FRD of 50 $μ$ m core fibre is substandard for the requirement which requires the output focal ratio to be slower than 4.5. The homogeneity of throughput is acceptable and higher than 85 per cent. The prototype IFU of the first generation helps to find out the imperfections to optimize the new design of the next generation based on the staggered structure with 35 $μ$ m core fibres of N.A. = 0.12, which can improve the FRD performance. The FRD dependence on wavelength and core size is revealed that higher output focal ratio occurs at shorter wavelengths for large core fibres, which is in agreement with the prediction of PDM. But the dependence of the observed data is weaker than the prediction.